2011
DOI: 10.1093/eurheartj/ehq521
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Apolipoprotein A-1 auto-antibodies are active mediators of atherosclerotic plaque vulnerability

Abstract: These results suggest that anti-ApoA-1 IgG might be associated with increased atherosclerotic plaque vulnerability in humans and mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
229
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 118 publications
(253 citation statements)
references
References 27 publications
17
229
6
1
Order By: Relevance
“…148 A few years later, Vuilleumier et al found that 11-21% of ACS patients tested positive for anti-apoA-I autoantibodies compared with 20% of patients with severe internal carotid stenosis, 38% of non-STEMI patients, 29% of patients undergoing elective carotid endarterectomy, and 1-2% of healthy controls. [149][150][151][152] In fact, there was an association between high anti-apoA-I IgG titers and increased circulating levels of oxidized LDL, TNF-α, IL-6, IL-8, and matrix metalloproteinase 9 (MMP-9). 150,153,154 Accordingly, patients positive for serum anti-apoA-I IgG had decreased plaque stability, as evidenced by increased intraplaque MMP-9 levels as well as higher densities of macrophages and neutrophils within plaques.…”
Section: Anti-apoa-i Autoantibodiesmentioning
confidence: 99%
See 3 more Smart Citations
“…148 A few years later, Vuilleumier et al found that 11-21% of ACS patients tested positive for anti-apoA-I autoantibodies compared with 20% of patients with severe internal carotid stenosis, 38% of non-STEMI patients, 29% of patients undergoing elective carotid endarterectomy, and 1-2% of healthy controls. [149][150][151][152] In fact, there was an association between high anti-apoA-I IgG titers and increased circulating levels of oxidized LDL, TNF-α, IL-6, IL-8, and matrix metalloproteinase 9 (MMP-9). 150,153,154 Accordingly, patients positive for serum anti-apoA-I IgG had decreased plaque stability, as evidenced by increased intraplaque MMP-9 levels as well as higher densities of macrophages and neutrophils within plaques.…”
Section: Anti-apoa-i Autoantibodiesmentioning
confidence: 99%
“…150,153,154 Accordingly, patients positive for serum anti-apoA-I IgG had decreased plaque stability, as evidenced by increased intraplaque MMP-9 levels as well as higher densities of macrophages and neutrophils within plaques. 151 These clinical findings are corroborated by in vivo and in vitro data showing that apoE-deficient mice immunized with anti-apoA-I IgG developed larger, more vulnerable atherosclerotic lesions with higher neutrophil and MMP-9 contents and reduced collagen content, displayed signs of myocardial injury, and had higher mortality rates than apoEdeficient mice treated with a control IgG. 151,155 Furthermore, incubation of human monocytederived macrophages with anti-apoA-I IgG under cell culture conditions resulted in increased production of cytokines (TNF-α, IL-6, IL-8), matrix metalloproteinases (MMP-9), and monocyte chemoattractants (CCL2, CXCL8).…”
Section: Anti-apoa-i Autoantibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…18,22 The fold change of mRNA levels was calculated by the comparative C t method. The measured C t values were first normalized to the Hprt internal control, by calculating a delta C t (DC t ).…”
Section: Real-time Rt-pcrmentioning
confidence: 99%